2011
DOI: 10.1007/s12105-011-0261-3
|View full text |Cite
|
Sign up to set email alerts
|

Cemento-Osseous Dysplasia-Like Lesion and Complex Odontoma Associated with an Impacted Third Molar

Abstract: We present a case of a 36-year-old female with a benign fibro-osseous lesion consistent with cementoosseous dysplasia (COD) that was located coronally to the crown of an impacted mandibular third molar tooth and was associated with a complex odontoma. The pathogenesis of this unusual association is discussed and the odontogenic origin of COD is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…10 Infrequently, the aggregation of an odontoma and transmigrated canine has led to the impaction of additional adjacent teeth, including a premolar or lateral incisor. 14,15 Prodromidis et al 16 2 with biopsy-proved dentigerous cyst formation. 22,23 It is advised that oral cystic-appearing tissue undergo histopathologic assessment for diagnosis and rule out a malignant process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Infrequently, the aggregation of an odontoma and transmigrated canine has led to the impaction of additional adjacent teeth, including a premolar or lateral incisor. 14,15 Prodromidis et al 16 2 with biopsy-proved dentigerous cyst formation. 22,23 It is advised that oral cystic-appearing tissue undergo histopathologic assessment for diagnosis and rule out a malignant process.…”
Section: Discussionmentioning
confidence: 99%
“…Prodromidis et al 16 reported focal COD proximate to a complex odontoma and impacted third molar, questioning whether this was a causal or casual relationship. Similarly, Borghesi et al 17 recorded a case of focal COD; compound odontoma; peripheral osteoma; and cemento‐ossifying fibroma; attributing their concurrence to chance, hormonal imbalance or genetic process.…”
Section: Discussionmentioning
confidence: 99%
“…Compound odontomas may appear as tooth like structures containing enamel, dentine, cementum, and pulp and may be single or multiple [ 4 ]. Complex odontomas appear as a disorganized amorphous mass of calcified hard tissues [ 4 , 5 ]. Both lesions usually present in the first two decades of life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%